2018
DOI: 10.1017/s0144686x18000752
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of care among people aged 65–85 with cognitive impairment in the Netherlands

Abstract: Observation of long-term trends within countries is needed to increase insight into how policy initiatives are reflected in the use of care over time in addition to individual determinants of care use. In the past decades, Dutch care policies have favoured homecare and reduced the availability of institutional care which extended the care responsibilities of formal and informal care-givers at home. This study investigates the changes in the use of informal and formal homecare, community services and residentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…For example, in Sweden, studies have indicated that a reduction in formal LTC use corresponded to an increase in informal LTC use (Johansson et al, 2003; Sundström et al, 2006). Studies in the Netherlands have found that in the context of governmental LTC restriction policy and decreased availability of informal care, a decrease in informal LTC use did not lead to an increase in formal LTC use; instead, it resulted in an increased number of people receiving no LTC (Aaltonen et al, 2020; Swinkels et al, 2016). A study in Britain indicated that informal LTC increased to compensate for a sizeable decline in in‐home formal LTC during the investigation period (Patsios, 2008).…”
Section: Studies On Trends In Formal and Informal Ltcmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Sweden, studies have indicated that a reduction in formal LTC use corresponded to an increase in informal LTC use (Johansson et al, 2003; Sundström et al, 2006). Studies in the Netherlands have found that in the context of governmental LTC restriction policy and decreased availability of informal care, a decrease in informal LTC use did not lead to an increase in formal LTC use; instead, it resulted in an increased number of people receiving no LTC (Aaltonen et al, 2020; Swinkels et al, 2016). A study in Britain indicated that informal LTC increased to compensate for a sizeable decline in in‐home formal LTC during the investigation period (Patsios, 2008).…”
Section: Studies On Trends In Formal and Informal Ltcmentioning
confidence: 99%
“…Second, few studies have examined differences in the trends in LTC use by the characteristics of older adults with disabilities. Only one study has examined this issue (Aaltonen et al, 2020). In studies on LTC use in older adults, those with low functional capacity, who are living alone, are women and have a high income are associated with higher use of formal LTC than compared with those with high functional capacity, who are living with others, are men and have a low income (Blomgren et al, 2008; Katz et al, 2000).…”
Section: Studies On Trends In Formal and Informal Ltcmentioning
confidence: 99%
“…First of all, regarding the evaluation indicators of incapacitated subjects (6)(7)(8), most studies use single-dimensional scales for measurement, such as the commonly used Barthel, Lawton, and Brody instrumental daily activity scales and the Katz Scale, and the international function/disability and health-grading ICF and InterRAI evaluation systems which are more commonly used in OECD countries (9,10). There are also studies based on activities of daily living (ADL) and instrumental activities of daily living (IADL) (11)(12)(13)(14). Secondly, in most studies, the macrosimulation prediction method and micro-simulation prediction method are used to study the transition probability of failure state.…”
Section: Literature Reviewmentioning
confidence: 99%